MINAT SISWA DALAM MENGIKUTI EKSTRA KURIKULER FUTSAL - BUDIONO, TIAR (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical sport education and health is part of the educational curriculum provided in elementary school until the level of Senior High School. With the physical sport education and health in school, especially high school, students are able to aplicate their capabilities. Many lesson matter in physical sport education and health, there are one lesson  material is  futsal. Futsal is a material that can be obtained from the formal and non-formal education. In futsal learning process, teachers have an important role to increase the interest held by students. To determine the student's interests,  need to have direct information about the state of student interest. What doing is assess beyond the limited clues like face expressions and gestures. Under these conditions, the purpose of this research was to determine the